(3TQM GdgOGjIs - (3GdYjfis; (3GdYjfjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje aUd Ci gPG aVd ai HjGf eSGFd TJi ef CaYGd GdML PcQgG HaUd Ydi MOg dbdJgG HGdHGH aEf de jONd dMQe ecI hJhLg Edi YQaGJ hhba HgG s
(3BNQgG (B:s
(3UObg ai GdhdO KHJ fSHg hgh YHO dehdGg Je GdLRA GdKGdK ef GdHfGjI TQM GdgOGjI ddYjfi hjJdhg ai GdLRA GdQGHY cJGH GdEjeGf hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQSJ ddeNWhWs
(3HChdg Jedc HGSe YHO GdQGRb GdcjdGfi eDQN SfI (B1217(3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs